2014
DOI: 10.1371/journal.pone.0097017
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Approach to Activity Evaluation for Release-Active Forms of Anti-Interferon-Gamma Antibodies Based on Enzyme-Linked Immunoassay

Abstract: Selection of a suitable assay to measure the activity of drug agents based on release-active forms of anti-interferon-gamma antibodies (RA forms of Abs) is an important step forward in the investigation of such agents. In this study, the enzyme-linked immunosorbent assay was utilized to examine the effect of RA forms of Abs specific for human interferon gamma on the interaction between monoclonal anti-interferon gamma antibodies and recombinant human interferon gamma. The experimental data and the results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
2
15
0
1
Order By: Relevance
“…A dose–response relationship was confirmed by the statistical difference established for the antiviral activity of AC in comparison to the control group with the AC dose increment. This manner of action corresponds to the in vitro results obtained for this class of drugs [Gavrilova et al, ; Pschenitza et al, ; Gorbunov et al, ]. We also were able to determine the most appropriate dose and the direct correlation between dose of the virus inoculation and the suitable dose of the drug for treatment.…”
Section: Discussionsupporting
confidence: 78%
“…A dose–response relationship was confirmed by the statistical difference established for the antiviral activity of AC in comparison to the control group with the AC dose increment. This manner of action corresponds to the in vitro results obtained for this class of drugs [Gavrilova et al, ; Pschenitza et al, ; Gorbunov et al, ]. We also were able to determine the most appropriate dose and the direct correlation between dose of the virus inoculation and the suitable dose of the drug for treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The ability of R-A dilutions to modify properties of the original substance in vitro allowed us to apply other techniques besides spectroscopy (such as enzyme-linked immunosorbent assay, immune-sensory methods, and high performance liquid chromatography) for the evaluation of R-A drugs [29,52]. While developing analytical techniques, we found that common purified water subjected to the process of dilution ("processed" water) acquired new properties that were different from the intact water in pH, electrical conductivity, surface tension, speed of sound propagation, and spectral characteristics (data not published).…”
Section: The Problem Of the Nature Of Released-active Drugsmentioning
confidence: 99%
“…Some experimental studies indicate an effect of released activity (RA), implying that highly diluted active substances are capable of exerting modifying activity on their targets [57][58][59][60][61]. The physical mechanisms of RA are poorly studied, since small physical effects in highly diluted solutions are difficult to detect by physical and chemical methods, but lead to pronounced biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, a number of phenomena discovered experimentally can be of interest as a means of construction of mathematical models. An example is the investigation of the RA, annotated in [57][58][59][60][61]. The physical basis of this phenomenon is currently not clear, and the specificity of the phenomenon needs further research both at the structural and functional levels.…”
Section: Discussionmentioning
confidence: 99%